Piezoelectric antibacterial supramolecular self-gel hemostatic powder as well as preparation method and application thereof
By preparing piezoelectric antibacterial supramolecular self-gelling hemostatic powder and combining it with ultrasound therapy to regulate ROS generation, the problems of slow hemostasis and high infection risk of existing hemostatic materials in complex trauma environments have been solved, achieving rapid hemostasis and efficient antibacterial healing.
Patent Information
- Application Number
- CN202511318095.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-16
- Publication Date
- 2025-10-24
- Estimated Expiration
- 2045-09-16
AI Technical Summary
Existing hemostatic materials are slow to stop bleeding in complex trauma environments, have a high risk of infection, and take a long time to heal. Furthermore, there is a gap in the use of self-gel powder to address wounds infected with bacteria.
By preparing piezoelectric antibacterial supramolecular self-gelling hemostatic powder, a reversible hydrogel is formed by the synergistic effect of nanoclay, zwitterionic polymer, polyacrylic acid and piezoelectric nanoparticles. Combined with ultrasound therapy to regulate ROS generation, rapid hemostasis and efficient antibacterial healing are achieved.
It achieves rapid and effective hemostasis for irregularly shaped and high-pressure arterial bleeding wounds, significantly enhances adhesion to tissues, effectively kills wound bacteria, promotes cell proliferation and tissue regeneration, and shortens healing time.
Smart Images

Figure CN120827632A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a piezoelectric antibacterial supramolecular self-gelling hemostatic powder, a preparation method and application thereof, and belongs to the technical field of biomedical materials and wound repair. BACKGROUND
[0002] Uncontrollable bleeding and secondary infection of wounds caused by severe trauma have become a major challenge in the field of global public health, resulting in more than 5 million deaths worldwide each year. Traditional surgical suturing can effectively stop bleeding, but it has inherent defects such as high risk of secondary trauma, increased postoperative infection rate (about 37%), and scar formation. The commonly used hemostatic materials in clinical practice are difficult to adapt to irregular wounds due to insufficient adhesion, resulting in a significant decrease in hemostatic efficiency. How to achieve a dynamic balance between rapid hemostasis and controllable repair in a complex trauma environment has become a scientific problem that needs to be broken through in the fields of trauma first aid and regenerative medicine.
[0003] Adhesive hydrogels have been widely used in hemostatic agents, wound dressings, and wearable devices due to their excellent adhesion, mechanical properties, and biocompatibility. Adhesive hydrogels are mainly divided into two categories: pre-formed adhesive hydrogels and in-situ formed adhesive hydrogels. Pre-formed adhesive hydrogels require polymers to combine through tissue interfacial water diffusion, but most of these hydrogels rely on chemical cross-linking to stabilize the structure, resulting in weak adhesion between the tissue and the hydrogel. Self-gelling powders in in-situ formed adhesive hydrogels exhibit significant advantages due to their wet adhesion properties and rapid forming ability. Recent reports indicate that PEI / PAA / QCS self-gelling powders not only can rapidly stop bleeding, but also can promote the healing of full-thickness skin wounds. However, existing self-gelling powders still have gaps in dealing with bacterial infection wounds, which is a common and difficult problem in the treatment of severe trauma.
[0004] Sonoporation therapy (SPT) is a promising non-antibiotic therapy that uses ultrasound and a sonosensitizer to generate sufficient reactive oxygen species (ROS) to kill bacteria. It has recently become a promising method for treating bacterial infected wounds. Among them, barium titanate (BaTiO3, BTO) as a sonosensitizer with good piezoelectric effect has made great progress in antibacterial therapy. Its principle is that BTO can generate built-in electric field and surface potential under the action of ultrasound, thereby triggering redox reaction to generate ROS for antibacterial therapy. It is worth noting that although increasing local ROS levels helps to clear bacterial infection, excessive ROS can cause similar oxidative damage to adjacent cells and tissues, leading to local homeostasis imbalance and hindering subsequent repair. Therefore, precise regulation of ROS levels is the key to research. At present, the commonly used method to regulate ROS is to use antioxidants, but it is complex to determine the appropriate dose of antioxidants, and long-term use of antioxidants may interfere with normal cell signaling pathways and may trigger adverse reactions. Recently, controlling ultrasound to regulate ROS generation shows special potential. Ultrasound allows non-invasive and controllable ROS level adjustment through physical stimulation, optimizing cell proliferation and tissue regeneration while reducing adverse reactions. However, there is no study to determine the dose, frequency, and time dependence of ultrasound on the dose-effect relationship of treatment. Therefore, it is urgent to develop a supramolecular self-gel piezoelectric powder with adjustable ultrasound response for precise treatment of complex and difficult-to-heal wounds. SUMMARY
[0005] In view of the slow hemostasis speed, high risk of infection and long healing time in the prior art, the present application provides a piezoelectric antibacterial supramolecular self-gel hemostatic powder and a preparation method and application thereof. The precursor solution containing polyacrylic acid, zwitterionic polymer, nanoclay and piezoelectric nanoparticles is subjected to dry annealing and grinding treatment to prepare a piezoelectric antibacterial supramolecular self-gel hemostatic powder, which has excellent powder-gel reversibility and adjustable ultrasound responsiveness, solves the problems of rapid and effective hemostasis of acute bleeding, especially irregular, non-compressible and high-pressure arterial bleeding wounds, and low healing efficiency of bacterial infected wounds, and also can improve the defects of poor tissue adhesion, poor biocompatibility or single function that may exist in existing products, and provides a better solution for acute bleeding treatment and infected wound healing.
[0006] The piezoelectric antibacterial supramolecular self-gel hemostatic powder is obtained by drying and grinding a hydrogel, wherein, The hydrogel is uniformly dispersed in a network structure formed by supramolecular interaction of zwitterionic polymer and polyacrylic acid by nanoclay and piezoelectric nanoparticles; The zwitterionic polymer is [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl) ammonium hydroxide (DMAPS).
[0007] Further, the supramolecular interaction is one or both of hydrogen bonding or electrostatic interaction.
[0008] Further, the particle size of the hemostatic powder obtained after grinding is 100 mesh or more.
[0009] Preferably, the nanoclay is Laponite XLS.
[0010] Preferably, the piezoelectric nanoparticle is barium titanate.
[0011] In the method of the present application, the hydrogel is prepared by polymerization of the nanoclay, the zwitterionic polymer, the polyacrylic acid, the piezoelectric nanoparticle, and the deionized water.
[0012] Further, the mass ratio of the nanoclay, the zwitterionic polymer, the polyacrylic acid, and the piezoelectric nanoparticle is 1-3:25:1.5-3:0.015-0.025.
[0013] Further, the mass-to-volume ratio of the nanoclay and the deionized water is 1-3 g:10 mL.
[0014] Another object of the present application is to provide a method for preparing the hemostatic powder as described above, comprising the following steps: under stirring, the zwitterionic polymer, the polyacrylic acid, and the piezoelectric nanoparticle are sequentially added to the nanoclay suspension, and after stirring and mixing, a polymerization reaction is carried out, followed by drying and grinding to obtain the hemostatic powder.
[0015] In the above technical solution, the polymerization reaction conditions are 60°C for 45 min.
[0016] In the above technical solution, the stirring rate is 500 rpm, and the stirring and mixing time is 10 min.
[0017] In the above technical solution, the drying conditions are 60°C in an oven for 24 h.
[0018] In the above technical solution, the grinding is carried out using a ball mill, the ball-to-material ratio is 10:1, the grinding speed is 300 rpm, and the grinding time is 2 h.
[0019] Further, the nanoclay suspension is prepared by the following method: the nanoclay is added to the deionized water, and ultrasonic dispersion is carried out for 10 min.
[0020] Preferably, one of the technical solutions of the present application comprises the following steps: Step 1: The nanoclay is added to deionized water, ultrasonic dispersion is carried out, the nanoclay particles are uniformly distributed in the deionized water, and the occurrence of agglomeration is avoided, and finally a nanoclay water suspension with uniform texture is prepared; Step 2: After the water suspension in step 1 is stable, the stirring device is started, and under the condition of continuous stirring, the zwitterionic polymer, polyacrylic acid and piezoelectric nanoparticles are gradually added to the water suspension in sequence, and the stirring state is maintained for a period of time to ensure that the materials can be fully contacted and mixed to form a uniform mixed solution; Step 3: The mixed solution prepared in step 2 is carefully poured into the selected mold to ensure that the solution can uniformly fill the mold cavity, and then it is placed in a temperature-controllable device, and specific temperature parameters are set to make the mixed solution undergo polymerization reaction, and after the reaction is completed, a supramolecular hydrogel with a stable structure is obtained; Step 4: The hydrogel obtained in step 3 is taken out of the mold and placed in a drying device with a set temperature for drying treatment to remove the water in the hydrogel; after drying is completed, the dried hydrogel is ground using a grinding device to grind it into a powder with a particle size of 100 mesh or more, which is a piezoelectric antibacterial supramolecular self-gel hemostatic (DPNB) powder.
[0021] Another object of the present application is to provide the use of the above-mentioned hemostatic powder or the hemostatic powder prepared by the above-mentioned method in the preparation of a material for treating acute bleeding.
[0022] Another object of the present application is to provide the use of the above-mentioned hemostatic powder or the hemostatic powder prepared by the above-mentioned method in the preparation of a material for treating acute bleeding.
[0023] Further, the wound is a bacterial infectious wound.
[0024] The non-covalent interaction in the crosslinking of the supramolecular hydrogel can be flexibly broken and recombined, realizing excellent powder-gel reversibility. This makes the supramolecular hydrogel, after the structure is destroyed (such as in the process of dry annealing grinding), can quickly recover and re-form a stable network structure under environmental conditions (water / blood), which is more convenient for storage and transportation, and also provides a flexible and efficient solution for acute bleeding and irregular wound healing scenarios, significantly improving its practical value and adaptability.
[0025] The supramolecular self-gel hemostatic powder has adjustable ultrasonic responsiveness, and when it is used in combination with sonodynamic therapy, the synergistic effect of different intensity ultrasonic waves can be utilized to efficiently remove bacteria from the wound in the early stage and promote cell proliferation, migration and tissue regeneration in the later stage, realizing efficient antibacterial and accelerated healing of the wound after hemostasis. The specific combined use includes the following steps: Step 1: Pre-treat the infected wound and remove foreign matter from the surface. Then, apply the supramolecular self-gel hemostatic (DPNB) powder evenly to the wound surface, allowing it to fully contact the wound surface and form a hydrogel in situ, forming a physical barrier and adsorbing bacteria. Step 2: Implement the first stage of ultrasound treatment (antibacterial stage): Use high-intensity ultrasound to irradiate the wound area. The ultrasound triggers the piezoelectric catalytic effect of the DPNB powder to generate reactive oxygen species (ROS) to kill bacteria in the wound. Treatment is performed once a day until the bacteria are eliminated. Step 3: After completing the first stage of treatment, switch to the second stage of ultrasound treatment (healing promotion stage): use low-intensity ultrasound to irradiate the wound, and through the synergistic effect of mechanical stimulation and piezoelectric effect, promote fibroblast proliferation, migration and angiogenesis, accelerate granulation tissue formation and epithelialization, and treat once a day until the wound heals.
[0026] Preferably, in step 1, the amount of DPNB powder used is 20-30 mg per square centimeter of wound surface, and the hydrogel formation time is controlled within 3 s to quickly seal the wound and establish an antibacterial-repair microenvironment.
[0027] Preferably, in step 2, the parameters of the first stage of ultrasound treatment are: power 0.9 W / cm 2 The irradiation was performed at a frequency of 3 MHz, a duty cycle of 50%, and a daily irradiation time of 10 minutes for 3 days. During this phase, the sterilization rates of Escherichia coli and Staphylococcus aureus reached over 93%, without affecting cell proliferation and migration.
[0028] Preferably, in step 3, the parameters of the second stage ultrasound treatment are: power 0.3 W / cm 2 The irradiation time was 10 minutes per day, with a frequency of 3 MHz and a duty cycle of 50%, from day 3 to day 14. During this period, the number of fibroblast proliferation increased by about 2 times compared with the control group, the cell migration rate increased by about 3 times, and the number of angiogenesis was 5.7 times that of the control group.
[0029] Furthermore, the above technical solution can regularly observe the wound healing status, including the amount of exudate, wound closure rate and inflammatory response, and adjust the ultrasound treatment parameters according to the healing progress to ensure a balance between antibacterial effect and tissue repair.
[0030] Preferably, the wound observation cycle is once a day, and the closure rate is recorded through wound photos. The wound bacterial count (CFU count), collagen deposition rate and epidermal thickness are detected on the 3rd, 7th and 14th days respectively. Among them, the wound closure rate of the DPNB segmented ultrasound group on the 14th day can reach 96.3%, the epidermal thickness is close to that of normal skin (99.7 μm), and the collagen deposition rate reaches 67.2%.
[0031] Compared with the prior art, the present application has the following advantages: The supermolecular self-gelling hemostatic powder of the present application utilizes the synergistic effect of nanoclay, zwitterionic polymer, polyacrylic acid (PAA) and piezoelectric nanoparticles, so that it can form a hydrogel in situ through supermolecular interaction after contacting with blood, not only rapidly sealing the bleeding point, but also significantly enhancing the adhesion to the tissue through the hydrogen bond and electrostatic attraction formed by the free-COOH group, the positive charge quaternary ammonium salt group and the negative charge sulfonic acid group on the surface of the tissue, and forming a stable physical barrier to resist blood pressure, effectively coping with various complex bleeding scenarios, and having significant advantages in rapid hemostasis and complex wound adaptation, solving the problems of slow hemostasis speed and poor treatment effect on irregular shape or high pressure arterial wound of the existing hemostatic materials.
[0032] The DPNB powder of the present application has piezoelectric properties, which can realize efficient synergy of antibiosis and healing in combination with the spatio-temporal acoustic dynamic regulation therapy, specifically: in the early stage, high-intensity ultrasound is used to trigger the piezoelectric nanoparticles in the DPNB powder to generate piezoelectric effect, generating reactive oxygen species (ROS) to kill wound bacteria efficiently; in the later stage, low-intensity ultrasound is used to promote fibroblast proliferation, migration and angiogenesis through mechanical stimulation and piezoelectric effect, accelerating tissue regeneration, overcoming the limitations of insufficient antibiosis effect or long healing period in the prior art. BRIEF DESCRIPTION OF DRAWINGS
[0033] Figure 1 The figure is the structure test result of the supermolecular hydrogel and hemostatic powder obtained in Example 1, wherein a is a schematic diagram of the rapid self-gelation of the hemostatic powder to form various shapes, b is a micro self-gelation process diagram of the hemostatic powder, c is a scanning rheology test result diagram of the hemostatic powder, d is a frequency scanning rheology test result diagram of the hemostatic powder, and e is an FTIR test result diagram of the supermolecular hydrogel.
[0034] Figure 2 The figure is the adhesion test result of the supermolecular self-gelling powder, wherein a is an adhesion test result diagram of the supermolecular hydrogel containing different PAA contents on pig skin, and b is an adhesion test result diagram of the supermolecular hydrogel obtained in Example 1 on different tissues.
[0035] Figure 3 The figure is the burst pressure test result of the supermolecular self-gelling powder, wherein a is a burst pressure test schematic diagram, and b is a burst pressure test result diagram of the DPNB powder containing different PAA contents.
[0036] Figure 4 The figure is the coagulation experiment result of the supermolecular self-gelling powder, wherein a is a coagulation experiment photo of the DPNB powder, and b is a coagulation time result diagram of the DPNB powder.
[0037] Figure 5 SEM images of supermolecular self-gel powder adhesion aggregation.
[0038] Figure 6 Graph of red blood cell adhesion rate of supermolecular self-gel powder.
[0039] Figure 7 Graph of supermolecular self-gel powder for rat liver hemostasis, wherein a is a schematic diagram and a photograph of DPNB powder for rat liver hemostasis, b is a bleeding amount result graph of DPNB powder for rat liver hemostasis, and c is a hemostasis time result graph of DPNB powder for rat liver hemostasis.
[0040] Figure 8 Graph of supermolecular self-gel powder for rat femoral artery hemostasis, wherein a is a schematic diagram and a photograph of DPNB powder for rat femoral artery hemostasis, b is a bleeding amount result graph of DPNB powder for rat femoral artery hemostasis, and c is a hemostasis time result graph of DPNB powder for rat femoral artery hemostasis.
[0041] Figure 9 Graph of supermolecular self-gel powder for rat tail hemostasis, wherein a is a schematic diagram and a photograph of DPNB powder for rat tail hemostasis, b is a bleeding amount result graph of DPNB powder for rat tail hemostasis, and c is a hemostasis time result graph of DPNB powder for rat tail hemostasis.
[0042] Figure 10 Graph of supermolecular self-gel powder ESR test results, wherein a is a •OH generation result graph, b is 1 O2 generation result graph.
[0043] Figure 11 Graph of supermolecular self-gel powder ROS content test results, wherein a is a TA measurement •OH production content graph, b is a SOSG measurement 1 O2 production content graph.
[0044] Figure 12 Graph of supermolecular self-gel powder ROS production under different ultrasonic powers, wherein a is a •OH generation result graph under different ultrasonic powers, b is a 1 O2 generation result graph.
[0045] Figure 13 Bacteriostasis graph of supermolecular self-gel powder with different ingredients.
[0046] Figure 14 Graph of bacteriostasis rate of supermolecular self-gel powder with different ingredients, wherein a is a bactericidal rate result graph of different treatment groups on Escherichia coli, and b is a bactericidal rate result graph of different treatment groups on Staphylococcus aureus.
[0047] Figure 15 Bacteriostatic graph of supramolecular self-gel powder under different ultrasonic power.
[0048] Figure 16 Bacteriostatic rate graph of supramolecular self-gel powder under different ultrasonic power, wherein a is the bactericidal rate graph of DPNB powder on Escherichia coli under different ultrasonic power, and b is the bactericidal rate graph of DPNB powder on Staphylococcus aureus under different ultrasonic power.
[0049] Figure 17 Cell proliferation graph of supramolecular self-gel powder with different components.
[0050] Figure 18 Relative cell proliferation number graph of supramolecular self-gel powder with different components.
[0051] Figure 19 Cell proliferation graph of supramolecular self-gel powder under different ultrasonic power.
[0052] Figure 20 Relative cell proliferation number graph of supramolecular self-gel powder under different ultrasonic power.
[0053] Figure 21 Cell migration graph of supramolecular self-gel powder with different components.
[0054] Figure 22 Cell migration gap area rate graph of supramolecular self-gel powder with different components.
[0055] Figure 23 Cell migration graph of supramolecular self-gel powder under different ultrasonic power.
[0056] Figure 24 Cell migration gap area rate graph of supramolecular self-gel powder under different ultrasonic power.
[0057] Figure 25 In vivo wound healing result graph of supramolecular self-gel powder.
[0058] Figure 26 In vivo wound area change graph under supramolecular self-gel powder treatment.
[0059] Figure 27 In vivo wound closure rate result graph under supramolecular self-gel powder treatment.
[0060] Figure 28 Wound tissue H&E staining result graph after supramolecular self-gel powder treatment.
[0061] Figure 29 Wound epidermis thickness result graph after supramolecular self-gel powder treatment.
[0062] Figure 30 Masson staining result of the wound tissue after treatment with the supramolecular self-gelling powder.
[0063] Figure 31 Wound thickness and collagen deposition rate result after treatment with the supramolecular self-gelling powder, wherein a is the result of Masson staining analysis of wound thickness, and b is the result of Masson staining analysis of collagen deposition rate.
[0064] Figure 32 Immunohistochemical staining result of Col I and Col III of the wound tissue after treatment with the supramolecular self-gelling powder.
[0065] Figure 33 Content and proportion of Col I and Col III collagen of the wound tissue after treatment with the supramolecular self-gelling powder, wherein a is the content of type I collagen (Col I), b is the content of type III collagen (Col III), and c is the proportion of the content of type I collagen to the content of type III collagen.
[0066] Figure 34 Expression result of inflammatory iNOS protein and anti-Arg protein of the wound tissue after treatment with the supramolecular self-gelling powder, wherein a is the immunofluorescence staining of inflammatory iNOS protein and Arg1 protein, b is the content of Arg1, and c is the content of iNOS.
[0067] Figure 35 Expression result of inflammatory cytokines IL6 and IL10 of the wound tissue after treatment with the supramolecular self-gelling powder, wherein a is the content of IL-6, and b is the content of IL-10.
[0068] Figure 36 Immunofluorescence staining result of the wound tissue after treatment with the supramolecular self-gelling powder.
[0069] Figure 37 Relative blood vessel number result of the wound tissue after treatment with the supramolecular self-gelling powder. DETAILED DESCRIPTION
[0070] The following non-limiting examples can make those of ordinary skill in the art more fully understand the present application, but in no way limit the present application.
[0071] The test methods described in the following examples are all conventional methods unless otherwise specified; the reagents and materials described in the following examples can be obtained from commercial channels unless otherwise specified.
[0072] Example 1 A preparation method of a piezoelectric antibacterial supramolecular self-gelling hemostatic powder (DP3NB), comprising the following steps: (1) preparing a nanoclay suspension: 0.2 g Laponite XLS is added into 1 mL deionized water, and ultrasonic dispersion is performed for 10 min to obtain a uniform water suspension; (2) preparing a mixed solution: 2.5 g DMAPS, 0.25 g PAA and 2 mg BTO are sequentially added into the above suspension under stirring at 500 rpm, and stirring is performed for 10 min until the components are fully mixed to obtain a mixed solution; (3) polymerization and drying: the mixed solution is poured into a silica gel mold, 60°C polymerization is performed for 45 min to form a supramolecular hydrogel (DPNB hydrogel), and after 60°C oven drying for 24 h, a ball mill is used for grinding (ball-to-material ratio 10:1, rotation speed 300 rpm, grinding for 2 h) to obtain a powder, which is named as DP3NB.
[0073] Example 2 The difference between this example and Example 1 is that in step (2), DMAPS is 2.5 g, PAA is 0.15 g, and BTO is 2 mg, and the finally obtained powder is named as DP1NB.
[0074] Example 3 The difference between this example and Example 1 is that in step (2), DMAPS is 2.5 g, PAA is 0.2 g, and BTO is 2 mg, and the finally obtained powder is named as DP2NB.
[0075] Example 4 The difference between this example and Example 1 is that in step (2), DMAPS is 2.5 g, PAA is 0.3 g, and BTO is 2 mg, and the finally obtained powder is named as DP4NB.
[0076] The supramolecular hydrogel and hemostatic powder DP3NB obtained in Example 1 are subjected to structure testing, and the results are shown in Figure 1 : From Figure 1 a, it can be seen that when phosphate buffer solution (PBS) is added to the DPNB powder of different shapes, the powder will swell rapidly by itself to form a physically cross-linked supramolecular hydrogel with shape adaptability, and without any additional complex preparation steps.
[0077] In order to further study the self-gelling effect of the DPNB powder, the process of the powder contacting with PBS solution and transforming into a supramolecular hydrogel is observed under a microscope, and the results are shown in Figure 1 b, it can be seen that the DPNB powder rapidly absorbs water, swells and connects with each other, and forms a blocky hydrogel in about 3 seconds.
[0078] The gelation time of DPNB powder was determined by time sweep rheological test, and the results are shown in Figure 1 c, it can be seen that the storage modulus (G') curve intersects with the loss modulus (G'') curve at about 3 seconds, indicating that the powder can complete the transformation to hydrogel within 3 seconds, showing the potential of rapid sealing of bleeding points. In addition, the frequency sweep rheological test shows that the storage modulus (G') is significantly greater than the loss modulus (G''), and the storage modulus does not change with frequency Figure 1 d, which indicates that the DPNB hydrogel has typical elastic behavior and solid state characteristics, further confirming that the stable hydrogel network is formed only by physical interaction.
[0079] Fourier transform infrared (FTIR) spectroscopy further reveals the cross-linking mechanism of DPNB hydrogel, and the results are shown in Figure 1 e, it can be seen that the carboxyl (—COOH) peak at 1635 cm -1 and the amino (—NH2 or —NH) peak at 3480 cm -1 in DMAPS are shifted to 1710 cm -1 and 3450 cm -1 in DPNB, respectively. The shift of these absorption peaks reflects the change of intermolecular interaction, confirming the existence of hydrogen bonding and electrostatic interaction. However, since no new characteristic peak appears, it further verifies that the DPNB hydrogel is cross-linked by supramolecular interaction rather than covalent bond.
[0080] The adhesion performance test of the supramolecular hydrogel obtained in Examples 1-4 is shown in Figure 2 and Figure 3 : The shear strength of the hydrogel and pig skin was determined by shear test, and the maximum pressure when the powder sealing on the 2 mm hole of pig skin failed was determined by burst pressure test.
[0081] Results analysis: Figure 2 It shows that the hydrogel obtained in Example 1 achieves good adhesion, and the shear adhesion strength reaches 112 kPa, and its adhesion will increase with the increase of the content of PAA. Therefore, Example 1 is significantly higher than Example 2 (60 kPa) and Example 3 (70 kPa), and lower than Example 4 (140 kPa), because PAA can form strong hydrogen bonding with the amine group on the tissue surface through the carboxyl group. Figure 3The burst pressure of the hydrogel obtained in Example 1 was as high as 285 mmHg, much higher than that of Example 2 (90 mmHg), Example 3 (120 mmHg) and Example 4 (160 mmHg). The excess of PAA would result in the decrease of burst pressure and weaken the sealing ability. In summary, the adhesion performance of the hydrogel obtained in Example 1 (DP3NB) was the best.
[0082] Example 5 The difference between this example and Example 1 is that in step (1), 0.1 g Laponite XLS was added into 1 mL deionized water, and the final powder was named as DPN1B.
[0083] Example 6 The difference between this example and Example 1 is that in step (1), 0.3 g Laponite XLS was added into 1 mL deionized water, and the final powder was named as DPN3B.
[0084] The hemostatic powders obtained in Examples 1, 5 and 6 were tested for coagulation performance, and the results are shown in Figures 4-6 : The powders were mixed with whole blood, and the time for forming a stable clot was recorded. The aggregation of red blood cells (RBC) on the surface of the powder was observed by SEM, and the RBC adhesion rate was calculated. The test without adding any powder was taken as the control group (Control), and the whole blood was directly placed in the same environment for testing, to obtain the basic coagulation time and RBC natural state data, as the baseline for performance comparison; the powder without PAA was named as DP0NB powder (the remaining operations were the same as Example 1); the powder without nano-clay was named as DPN0B powder (the remaining operations were the same as Example 1).
[0085] Result analysis: The in vitro coagulation ability of DPNB powder was evaluated by measuring the coagulation time after mixing with whole blood, and the results are shown in Figure 4 , it can be seen that the coagulation time of the control group was about 7 minutes, and both DP0NB and DPN0B groups had certain coagulation ability, and they formed stable clots within 60 s and 300 s, respectively, indicating that the adhesion of PAA and the coagulation of XLS could both accelerate the formation of clots, and the effect of XLS was more significant, therefore, the coagulation ability of DPNB powder with different concentrations of XLS was mainly studied. With the increase of XLS content, the coagulation time of DPNB powder was significantly shortened to about 20 s, and the coagulation time of DPN3B group increased again, which might be because the excessive cross-linking of nano-clay affected the polymerization of DPNB powder and weakened the coagulation performance. The adhesion and aggregation of red blood cells (RBC) played a key role in blood coagulation and hemostasis, and the morphology of the adhered red blood cells was characterized by obtaining scanning electron microscope images, and the results are shown in Figure 5and Figure 6 It can be seen that a large number of RBCs adhere to the DPNB powder, and DP3NB shows a larger and denser aggregation of RBCs Figure 5 ); At the same time, the red blood cell adhesion test further shows that the red blood cell adhesion rate of the DP3NB group is the highest, reaching 90.4% Figure 6 Therefore, the in vitro hemostatic performance of the DP3NB powder is the best.
[0086] The hemostatic powder DP3NB obtained in Example 1 was subjected to in vivo hemostatic testing, and the results are shown in Figures 7-9 : A rat liver partial resection model (resection of liver lobe), femoral artery puncture model (puncture of femoral artery), and tail vein transection model (transection of tail vein) were established; the powder was uniformly coated on the surface of each model wound, and the hemostatic time and blood loss were recorded. The test without adding any powder was taken as the blank group (Control) to obtain the state data of the self hemostatic time and blood loss, which served as the baseline for performance comparison. Commercial chitosan powder was taken as the control group.
[0087] Results analysis: The in vivo hemostatic performance of the DPNB powder was verified in the rat non-compressible liver bleeding model, and the results are shown in Figure 7 It can be seen that in the rat liver partial resection model with incision, the blank group without any treatment bled severely, with a maximum blood loss of 902 mg and a longest hemostatic time of 317 s; after using the traditional hemostatic material chitosan and DPNB powder on the wound site, the blood loss (412 mg and 224 mg, respectively) and hemostatic time (197 s and 40 s, respectively) of each group were reduced. Large vessel injury is usually accompanied by rapid pressurized blood flow and fatal bleeding, and the rat femoral artery bleeding model was used to further verify the hemostatic ability of the DPNB powder, and the results are shown in Figure 8 It can be seen that after puncturing the femoral artery, the traditional chitosan cannot stop the arterial bleeding, while the DPNB powder can quickly absorb blood and form a solid sealing layer, with the fastest hemostatic time within 20 s and no secondary bleeding during the observation period; compared with the blank group, the blood loss of the DPNB group was reduced by 70%. The same trend was also observed in the mouse tail transection model, and the results are shown in Figure 9 It can be seen that chitosan cannot stop the tail bleeding, while DPNB powder can quickly stop bleeding within 45 s, and the hemostatic amount is much smaller than that of the blank group. These results show that the DPNB hydrogel can withstand the pressure of arterial rupture and has the ability to stop bleeding in high-pressure arteries. In summary, the in vivo hemostatic performance of the DP3NB powder is the best.
[0088] The piezocatalytic performance test of the hemostatic powder DP3NB obtained in Example 1 was performed, and the results are shown in Figures 10-12 : The powder was dispersed in PBS at 0.3~1.2 W / cm 2 Irradiate under ultrasound for 10 min, and use TA probe (react with •OH to generate fluorescent HTA) and SOSG probe (react with 1 O2 reaction to generate fluorescent products), and the OH and 1 The amount of O2 generated. The test without adding any powder was used as the blank group (Control) and served as the baseline for the comparison of piezoelectric catalytic performance; the powder obtained without adding BTO was named DPN powder.
[0089] Results: The generation of ROS was confirmed by electron spin resonance (ESR) measurement. Figure 10 , 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) and 2,2,6,6-tetramethyl-4-piperidone (TEMP) were used as •OH and 1 The spin trapping mixture of O2 shows the typical 1:2:2:1 quartet signal of DMPO-OH and 1:1:1 triplet signal of TEMPONE. The piezoelectric catalytic ability of DPNB powder to generate ROS under ultrasonic stimulation is shown in Figure 11 , the production content of hydroxyl radicals (•OH) was measured by phthalic acid (TA). TA was used as a probe molecule to react with •OH to generate fluorescent 2-hydroxyterephthalic acid (HTA). It can be seen that: when the irradiation time of DPNB powder under ultrasonic stimulation increased from 0 minutes to 10 minutes, the fluorescence intensity of HTA at 426 nm gradually increased; especially under 10 minutes of ultrasonic stimulation, the fluorescence intensity was 3.5 times that of 1 minute, indicating that the generation of •OH was time-dependent; at the same time, under the same ultrasonic stimulation conditions, DPNB produced more •OH than DPN, confirming the importance of BTO in the piezoelectric catalytic effect of self-gel powder. In addition, a commercial ROS fluorescent probe singlet oxygen sensor green (SOSG) was used to measure singlet oxygen ( 1 Under ultrasonic stimulation, DPNB powder showed better 1 The O2 generation capacity of SOSG was significantly improved, and the fluorescence intensity of SOSG at 540 nm gradually increased with the increase of ultrasound time. The ultrasound intensity has a significant effect on the generation of ROS. The results are shown in Figure 12 It can be seen that when the ultrasonic power is increased from 0.3 W / cm 2 Increased to 1.2 W / cm 2 When the •OH ( Figure 12 a) and 1 O2 ( Figure 12b) all significantly increased, which also indicated that the content of ROS could be controlled by the intensity of ultrasound. In summary, it was confirmed that the DPNB powder had excellent piezocatalytic ability to generate ROS under ultrasound.
[0090] The antibacterial performance of the hemostatic powder DP3NB obtained in Example 1 was tested, and the results are shown in Table 2. Figures 13-16 After the E. coli and S. aureus suspensions were co-cultured with the powder for 1 h, the bacteria were irradiated with 0.3-1.2 W / cm 2 ultrasound (US) for 10 min, or without US, and the sterilization rate was calculated by agar plate colony counting method. The test without adding any powder was taken as the blank group (Control) as the baseline for antibacterial performance comparison; the test without adding any powder and with only US (Control+US) was taken as the baseline for US antibacterial performance comparison; the powder obtained without adding BTO was named as DPN powder.
[0091] Results analysis: As can be seen from Figure 13 and Figure 14 : compared with the group without using US irradiation, the survival rates of E. coli and S. aureus in the US irradiation group decreased; the sterilization ability of the Control+US group and the DPN+US group was weak, and the potential mechanism might be the mechanical damage and cavitation effect of US; after 10 min of US stimulation, the number of bacterial colonies on the agar plate in the DPNB+US group decreased to about 5%, showing a very strong sterilization effect. The antibacterial effect of the DPNB powder was also specifically verified by colony-forming unit (CFU) counting method. For E. coli, the sterilization rates of the Control group, the DPN group, the DPNB group, the Control+US group, the DPN+US group and the DPNB+US group were about 5.8%, 19.1%, 40.3%, 43.2% and 94.1%, respectively. For S. aureus, the sterilization rates of the Control group, the DPN group, the DPNB group, the Control+US group, the DPN+US group and the DPNB+US group were about 2.7%, 7.9%, 48.3%, 55.4% and 94.9%, respectively. The results showed that the ROS generated by the DPNB powder under the action of US could significantly improve the antibacterial effect. As can be seen from Figure 15 and Figure 16 : with the increase of US power, under the same irradiation time (10 min), the bacterial colonies gradually decreased, showing an ultrasonic intensity-dependent sterilization effect, and when the power increased from 0.3 W / cm 2 to 1.2 W / cm 2 When the ultrasonic power was increased to 0.9 W / cm 2 , the killing rates of E. coli and S. aureus reached 83.8% and 85.1%, respectively. In summary, the DPNB+US group showed ideal killing rates, confirming the excellent in vivo antibacterial effect of the DPNB powder under high-power ultrasound.
[0092] The hemostatic powder DP3NB obtained in Example 1 was subjected to cell proliferation and migration tests, and the results are shown in Figures 17-24 : (1) Cell proliferation test: L929 cells were co-cultured with powder extracts, and the OD 450 values (reflecting cell numbers) at 1 day, 3 days and 5 days were detected by CCK-8 method; after co-culture, 0.3 W / cm 2 ultrasound irradiation was performed for 10 min / day, or no ultrasound was performed, and the proliferation differences were compared.
[0093] (2) Cell migration test: a scratch test was used to make a scratch in the cell monolayer, and the powder extract was added; 0.3-1.2 W / cm 2 ultrasound irradiation was performed for 10 min, or no ultrasound was performed, and the scratch closure rates at 0 h, 12 h and 24 h were recorded.
[0094] The test of culturing L929 cells with only cell culture solution without adding any powder was used as a blank group; the test of culturing L929 cells with only cell culture solution without adding any powder, combined with ultrasound, was named Control+US; the test of not adding the powder obtained from BTO was named DPN powder.
[0095] Result analysis: the effect of the piezoelectric effect generated by the DPNB powder under the action of US on fibroblast proliferation was studied, and the results are shown in Figure 17 and Figure 18 . It can be seen that: the fibroblasts were cultured with DPN and DPNB powders for 24 hours, and then 0.3 W / cm 2The results of the cell growth effect of the US irradiation group were significantly more significant than those of the non-ultrasound treatment group. Specifically, after 5 days of culture, the relative cell numbers of the Control, DPN, DPNB, Control+US, DPN+US, and DPNB+US groups were 569, 673, 736, 913, 930, and 1138, respectively. It can be seen that the cell number of the DPNB+US group was much higher than that of the DPNB group, which indicated that the DPNB powder could promote cell proliferation under the piezoelectric effect of ultrasound. The effect of cell proliferation was also related to the ultrasound power, and the results are shown in Figure 19 and Figure 20 It can be seen that when the ultrasonic power was 0.3 W / cm 2 , the cell proliferation effect was the best, and the proliferation rate reached 894 on the 5th day; when the ultrasonic power continued to increase, the cell proliferation rate began to slow down, and the proliferation rates on the 5th day were 820 and 722 for 0.6 W / cm 2 and 0.9 W / cm 2 , respectively, but were still better than those of the control group; when the ultrasonic power increased to 1.2 W / cm 2 , the cell proliferation rate was lower than that of the control group. This indicated that high-intensity ultrasound could cause cell damage and death due to the generation of excessive ROS and excessive mechanical shock effect. In summary, it was confirmed that the DPNB powder had a promoting effect on cell proliferation under the action of low-intensity ultrasound.
[0096] The migration of fibroblasts cultured with DPNB powder was evaluated by scratch test, and the results are shown in Figure 21 and Figure 22 It can be seen that the DPNB+US group had the fastest wound closure speed and the smallest cell gap area of 7.5% after 24 hours of culture. In comparison, the cell gap areas of the Control group, DPN group, DPNB group, Control+US group, and DPN+US group were 25.8%, 17.4%, 16.9%, 12.4%, and 10.1%, respectively. This may be due to the fact that the DPNB generates appropriate concentrations of ROS and piezoelectric effects under ultrasound, which can adjust the local cytoskeleton at the molecular level and promote fibroblast migration through the activation of redox signaling cascades. Therefore, this also provides strong contraction force for the wound healing of the epidermis and subcutaneous tissue. The effect of different ultrasonic powers on fibroblast migration was observed, and the results are shown in Figure 23 and Figure 24 It can be seen that the cell migration was the most significant under the power of 0.3 W / cm 2 , and the cell gap area was 6.8% after 24 hours; the cell migration was 0.6 W / cm 2 and 0.9 W / cm 2The obvious cell migration was also observed, but the migration rate was significantly weakened, 10.9%, 21.6% respectively; at 1.2 W / cm 2 the cell migration effect (24.7%) began to be less than 0 W / cm 2 (22.6%), which may be due to the cell damage caused by excessive ultrasound intensity, thereby interfering with cell migration. In summary, it reveals the potential application value of DPNB powder in accelerating cell migration and promoting wound healing under the action of ultrasound.
[0097] Example 7 Application of the supramolecular self-gelling powder DP3NB obtained in Example 1 combined with spatiotemporal acoustic power regulation to achieve antibacterial healing, the results are shown in Figures 25-27 : A full-thickness infected wound model (diameter 1 cm, inoculated with 1×10 5 CFU of Staphylococcus aureus) was established on the back of a rat; the wound surface was coated with powder, without ultrasound, or treated with spatiotemporal acoustic power regulation: 0~3 days with 0.9 W / cm 2 ultrasound irradiation for 10 min / day (antibacterial stage), 4~14 days with 0.3 W / cm 2 ultrasound irradiation for 10 min / day (pro-healing stage); observed for 14 days and recorded the wound closure rate. Without adding any powder, as the baseline for comparison of wound healing performance, namely the Control group; without adding any powder, only ultrasound, as the baseline for comparison of wound healing performance of ultrasound, namely the Control+US group; the powder obtained without BTO was named as DPN powder.
[0098] Results analysis: from Figures 25-27 can be seen: in the first half of the treatment, 0~3 days with high-intensity US (0.9 W / cm 2 ) for antibacterial treatment. The wound around the DPNB+US group had less exudate, and the closure trend was the best, while the wound environment of the Control group and the Control+US group was poor, with visible deepening and covering a large amount of scab; the DPN group and the DPN+US group had weaker healing effect, which may be related to the provision of a moist environment conducive to wound healing; the DPNB+US group also obtained the best wound area closure rate of 45.5% on the 3rd day, which confirmed that high-intensity US (0.9 W / cm 2) promoted wound healing; the wound area closure rates of Control group, DPN group, DPNB group, Control+US group and DPN+US group were 4.8%, 17.0%, 31.1%, 14.2%, 33.6% on day 3. This shows that DPN powder and ultrasound treatment have a certain healing effect on infected wounds, and the DPNB+US group with piezoelectric effect has the best healing effect. At the same time, in the second half of the treatment, from day 3 to day 14, low-intensity US (0.3 W / cm 2 ) was used to accelerate wound healing. The wound area closure rates of Control group, DPN group, DPNB group, Control+US group, DPN+US group, DPNB+US group were 47.7%, 68.9%, 91.8%, 57.5%, 72.5%, 96.3% on day 14. It can be seen that the DPNB+US group has the fastest wound healing rate, and the wound almost disappears on day 14, which confirms that the piezoelectric effect of DPNB powder under low-intensity ultrasound is conducive to rapid cell proliferation and migration. In summary, this segmented sonodynamic therapy using high-intensity ultrasound to eliminate bacteria and low-intensity ultrasound to accelerate healing can reduce tissue damage, balance antibacterial and cell viability, and optimize the healing effect of infected wounds.
[0099] The wound tissue corresponding to Example 7 was collected for histological testing, and the results are shown in Figures 28-37 : H&E staining: observe the epidermis thickness, continuity and inflammatory cell infiltration; Masson staining: analyze the collagen deposition amount and arrangement direction; immunohistochemical staining: detect the content and ratio of collagen type I (Col I) and collagen type III (Col III); immunofluorescence staining: label vascular smooth muscle actin (α-SMA) and quantify the number of new blood vessels.
[0100] Result analysis: The H&E staining results are shown in Figure 28 and Figure 29 It can be seen that: the wound of the DPNB+US group has a thicker average epidermis thickness (99.7 μm), and the epidermis layer is more continuous and distinct in hierarchy, close to normal skin. In the subcutaneous tissue, neutrophils and lymphocytes are rare, while in the control group, more inflammatory infiltration and tissue fragments can be observed. This shows that DPNB powder with ideal bactericidal ability can improve the wound healing microenvironment. In addition, the tissue regeneration degree of the treatment groups using ultrasound or DPN powder is better than that of the control group, which also proves that the healing of the hydrogel itself and the mechanical stimulation of ultrasound can accelerate skin regeneration and wound recovery.
[0101] During the wound healing process, the relatively high density of collagen helps to increase the elasticity of the regenerated tissue, thus maintaining the physical continuity between the original and newly formed skin tissue. Masson staining was used to evaluate the collagen distribution at the wound site, and the results are shown in Figure 30 and Figure 31 As a component of the skin, the synthesis, deposition, and orientation of collagen play a crucial role in wound repair, and the presence of collagen deposition is beneficial to the healing process. Obviously, the DPNB+US group has more deposited and highly oriented collagen structure (67.2%), showing better extracellular matrix remodeling and epithelial tissue reconstruction.
[0102] Col I and Col III are important collagen types in connective tissue, playing a key role in different stages of wound healing. To further explore the mechanism of DPNB powder in promoting wound healing, immunohistochemical staining was used, and the results are shown in Figure 32 and Figure 33 It can be seen that the Col I and Col III collagen proteins in the DPNB+US group are 1.7 times and 2.3 times that of the Control group, respectively. Notably, the ratio of I / III type collagen is lower in the ultrasound treatment group, and the I / III type collagen ratio is the lowest in the DPNB+US group. This indicates that the DPNB powder not only promotes collagen deposition to accelerate healing, but also amplifies the ultrasound treatment to reduce scar tissue formation, which is beneficial to the remodeling of the collagen network.
[0103] To evaluate the inflammatory regulation of the powder on the wound tissue, immunofluorescence staining was used to detect the macrophage phenotype in each group, with inducible nitric oxide synthase (INOS) and arginase 1 (ARG1) used to label M1 and M2 macrophages, respectively, and the results are shown in Figure 34 and Figure 35 It can be seen that compared with the Control group, the DPNB+US group significantly reduces the expression of inflammatory iNOS protein and increases the secretion of anti-inflammatory Arg1 protein. (ELISA) detection also proves that the DPNB+US group has the least inflammatory cytokine IL6 and the most IL10 in the skin tissue, both indicating that the combination of DPNB powder and ultrasound can effectively reduce local inflammation, regulate the transformation of macrophages to anti-inflammatory M2 phenotype, and promote wound repair. In addition, angiogenesis is a key link in wound healing, as it helps to provide oxygen and nutrients, remove metabolic waste, support cell migration and proliferation, and promote granulation tissue formation, so immunofluorescence staining was performed on the angiogenesis marker (α-SMA), and the results are shown in Figure 36 and Figure 37It can be seen that the relative blood vessel number of the US group is more than that of the group without US, which shows that ultrasound can promote angiogenesis. The relative blood vessel number of the DPNB+US group is the most, which is 5.7 times of that of the control group, which shows that the DPNB powder combined with ultrasound can greatly accelerate the growth of new capillaries into the wound.
[0104] In summary, the piezoelectric antibacterial supramolecular self-gelling hemostatic powder is developed in the present application, which can quickly stop bleeding in irregularly shaped wounds and can be used as an effective wound dressing, and combined with the acoustic power optimization technology to play a comprehensive therapeutic role. When in contact with blood, the DPNB powder rapidly forms a hydrogel with strong adhesion through physical cross-linking. In addition, in various rat bleeding wound models, the DPNB powder can promote blood cell aggregation and achieve effective hemostatic effect. Notably, through the antibacterial healing technology based on the spatiotemporal acoustic power regulation, the active oxygen (ROS) generated by the piezoelectric catalysis of the DPNB powder is controlled, which further optimizes the healing scheme of infected wounds. Specifically, in the first 0~3 days of treatment, high-intensity ultrasound is used to remove bacteria from the wound; from the 3rd day to the 14th day, low-intensity ultrasound is used to further promote cell proliferation and migration, effectively remove bacteria from the wound, accelerate the process of the inflammatory stage, stimulate collagen deposition, enhance epidermal regeneration and angiogenesis, thereby reducing scar formation, achieving excellent wound repair effect, and ultimately improving healing efficiency. The new self-gelling supramolecular hemostatic powder provided in the present application combined with ROS regulation technology provides a new idea for refractory wound healing, which has important scientific value and broad clinical application prospects.
Claims
1. Piezoelectric antibacterial supramolecular self-gelling hemostatic powder, characterized in that: The self-gelling hemostatic powder is obtained by drying and grinding a hydrogel, wherein, The hydrogel is formed by uniformly dispersing nano-clay and piezoelectric nanoparticles in a network structure of zwitterionic polymer and polyacrylic acid through supramolecular interactions. The zwitterionic polymer is [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl) ammonium hydroxide.
2. The hemostatic powder according to claim 1, characterized in that: The nano-clay is Laponite XLS; the piezoelectric nanoparticles are barium titanate.
3. The hemostatic powder of claim 1, wherein: The supramolecular interactions are one or both of hydrogen bond or electrostatic interaction.
4. The hemostatic powder of claim 1, wherein: The hydrogel is prepared by polymerization reaction of nano-clay, zwitterionic polymer, polyacrylic acid, piezoelectric nanoparticles and deionized water, wherein the mass ratio of the nano-clay, zwitterionic polymer, polyacrylic acid and piezoelectric nanoparticles is 1-3:25:1.5-3:0.015-0.025, and the mass-volume ratio of the nano-clay and deionized water is 1-3 g:10 mL.
5. Process for the preparation of the haemostatic powder according to any one of claims 1 to 4, characterized in that: The zwitterionic polymer, polyacrylic acid and piezoelectric nanoparticles are sequentially added to the nano-clay suspension under stirring, and then the polymerization reaction is carried out after stirring and mixing, followed by drying and grinding to obtain the hemostatic powder.
6. The method of claim 5, wherein: The polymerization reaction condition is 60℃ for 45 min.
7. The method of claim 5, wherein: The stirring rate is 500 rpm, and the stirring and mixing time is 10 min.
8. The method of claim 5, wherein: The drying condition is 60℃ for 24 h in an oven.
9. The preparation method according to claim 5, characterized in that: The grinding is carried out by a ball mill with a ball-to-material ratio of 10:1 at a speed of 300 rpm for 2 h.
10. Use of the hemostatic powder of any one of claims 1-4 or prepared by the method of any one of claims 5-9 in the preparation of a material for treating acute bleeding and / or wound healing.
Citation Information
Patent Citations
Hemostatic composition and hemostatic device (variants)
CN107454851A
Chitosan / zwitter-ion and acrylic acid copolymer double network self-healing hydrogel and preparation method thereof
CN110372885A
Strong-adhesion microgel dry powder capable of spontaneously forming closed layer as well as preparation method and application of strong-adhesion microgel dry powder
CN114652887A
Methods and compositions for wound healing
US20150283287A1
Supramolecular hybrid hydrogels for burn and wound dressings
WO2024054562A2